Door-to-antibiotic Time and In-hospital Mortality of Elder Patients Presenting to Emergency Department with Sepsis; a Cross-Sectional Study - Siriwimon Tantarattanapong; Thanaporn Hemwej (Archives of Academic Emergency Medicine, 2021)
Introduction: The current international sepsis guideline recommends that administration of intravenous broad-spectrum antibiotics should be initiated within 1 hour of emergency department (ED) arrival for sepsis patients. This study aimed to evaluate the association between door-to-antibiotic time and in-hospital mortality of these patients.